KAJIAN KAPASITAS DAYA TAMPUNG SALURAN DRAINASE PADA JALAN KAREL SATSUIT TUBUN DALAM DI KOTA SAMARINDA - RANDI, MUHAMAT (KURVA S JURNAL MAHASISWA, 2017)
Karel Satsuit Tubun Street road in the neighborhood, Sidodadi is one of frequent flooding. channels on the area just wear artificial channels which already no longer able to hold rain water discharge are quite high. With not as the area to accommodate the then conducted the study on drainage channels in the area. by examining the existing drainage on Satsuit Tubun Street In Karel road then it will be useful to drain off rainwater and wastewater in the area to prevent the occurrence of flooding in the area or in the area of writing goals This study was to calculate the dimensions of existing and designing the drainage channels.            Using such an analysis, namely analysis of rainfall flood design discharge analysis analysis of the hydraulics of open channel by using the log method person, gumbel, to calculate the intesitas rainfall, rational methods to analyze the flood discharge design and analyze channel hydraulics by knowing the discharge stream at channels then used method of manning.By doing such analysis then obtained cross-section design for drainage that is the width of the lower channel (b) = 1 m, channel height (h) = 2 m, and the height of the Roman (w) = 0.60